Money laundering as a risk in the banking industry of Bangladesh : a study on the EXIM Bank Ltd. Rajuk Avenue Branch - Mevij, Khandakar (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.